The makeup artist handbook : techniques for film, television, photography, and theatre - Davis, Gretchen (Focal Press, 2012)
Get professional techniques usually known only by Hollywood makeup artists in this full-color, comprehensive book from accomplished makeup pros Gretchen Davis and Mindy Hall. The two come to you with impressive backgrounds in film and television industries--their projects have included Pearl Harbor, Rent, Stuart Little, and The Nanny Diaries, and Mindy Hall is fresh off her Academy Award win for her work on 2009's Star Trek. This new edition of The Makeup Artist Handbook offers even more illustrations to demonstrate techniques visually; fundamentals on topics such as beauty, time periods, black and white film; and up-to-date information on cutting-edge techniques like air brushing makeup for computer-generated movies, makeup effects, mold-making, lighting, and lots of information on how to work effectively in HD. Learn from the pros and hone your craft with this comprehensive book. . Gorgeous full color book shows how makeup artists make Hollywood stars look as good as they do, even in HD! . Get the inside track about how to work with the pros and all about set etiquette . Contains tips and techniques from a number of professional Hollywood makeup artists . Includes a full reference section with useful websites, business listings, and contacts . Award winning advice from co-author Mindy Hall, Academy Award winner for makeup for her work on Star Trek.